Search for lepton-flavour-violating decays of Higgs-like bosons - Aaij, Roel; Abellán Beteta, C.; Adeva, Bernardo; Adinolfi, Marco; Aidala, Christine A.; Ajaltouni, Ziad J.; Akar, Simon; Albicocco, Pietro; Albrecht, Johannes; Alessio, Federico; Alexander, Michael T.; Alfonso Albero, A.; et al. (The European physical journal. C, Particles and fields, 2018)
A search is presented for a Higgs-like boson with mass in the range 45 to 195GeV/c2GeV/c2\,{{GeV/}c^2} decaying into a muon and a tau lepton. The dataset consists of proton-proton interactions at a centre-of-mass energy of 8 TeV TeV~TeV, collected by the LHCb experiment, corresponding to an integrated luminosity of 2 fb −1 fb −1\,\text{ fb }^{-1}. The tau leptons are reconstructed in both leptonic and hadronic decay channels. An upper limit on the production cross-section multiplied by the branching fraction at 95% confidence level is set and ranges from 22pbpb\,{pb} for a boson mass of 45GeV/c2GeV/c2\,{{GeV/}c^2} to 4pbpb\,{pb} for a mass of 195GeV/c2GeV/c2\,{{GeV/}c^2}.